Effect of AGTR1 and BDKRB2 gene polymorphisms on atorvastatin metabolism in a Mexican population - Herrera Gonzalez, Sarahï; Martinez Treviño, Denisse; Aguirre Garza, Marcelino; Gómez Silva, Magdalena; Barrera Saldaña, Hugo Alberto; Baltazar Reyes, Rafael (2017)
Abstract. Discrepancies in the response to drugs are partially due to polymorphisms in genes involved in drug metabolism and transport. The frequency, pattern and impact of these polymorphisms vary among populations. In the present study, the pharmacokinetics and pharmacogenetics of atorvastatin (ATV) in a Mexican population were investigated. The study cohort exhibited differing ATV metabolizing phenotypes, and in subsequent allelic discrimination assays, single nucleotide polymorphisms in the angiotensinogen, angiotensin II type 1 receptor (AGTR1) and bradykinin B2 receptor (BDKRB2) genes were genotyped and their effects on the pharmacokinetic parameters of ATV were assessed. Additionally, association studies were performed to test for a correlation between metabolizing phenotypes and genetic variants. It was observed that carriers of the genotypes A/C and C/T in AGTR1 and BDKRB2 had higher area under the plasma concentration-time curve values from time 0 to the time of the last measurement and from time 0 extrapolated to infinity, and lower values of clearance of the fraction dose absorbed compared with homozygous carriers (P<0.05). Only the C/C genotype of BDKRB2 was associated with the fast metabolizer phenotype. These data suggest that AGTR1 and BDKRB2 are involved in ATV pharmacokinetics; a novel finding that requires confirmation in further studies.